Professional Teacher Language: Its Contexts, Functions, and Potential to Further Teachers' Professionalism - Manuela Schlick (Karolinum Press, 2022)
Much attention has been dedicated to the professional development of teachers and how their professional knowledge base is formed in teacher education, but little attention has been paid to the surface level of such measures, that is the professional language used and developed within teacher education. The first part of this article presents a definition of professional teacher language and provides overviews for its contexts and functions in order to conceptualise its role for teachers' professional development and its potential for teacher education. To further illustrate this potential, a cognitive-linguistic perspective is applied to discuss the relationship of practical teacher knowledge and its verbalisation. This touches on the fundamental question of what proportion and aspects of teachers' professional knowledge base can be made explicit through language and how language can help to form this knowledge base. The second part contextualises and discusses results from an empirical qualitative study of practitioner teachers' discussing their practice in a professional learning group. This illustrates one methodological approach to exploring how practitioners verbalise their decision making in practice within professional discourse in a professional learning community.